KARTU ELLIPS DI SUMBU X DAN Y MATERI IRISAN KERUCUT SEBAGAI MEDIA PEMBELAJARAN MATEMATIKA PEMINATAN SISWA KELAS XI MADRASAH ALIYAH NEGERI BINJAI - Siti Rohani (Universitas Negeri Medan, 2021)
Innovation in the media as a learning tool can also be used to improve the quality of education in accordance with the talents and abilities of teachers as educators and students as students. Therefore, the author tries to make a learning tool as a medium for learning mathematics with specialization in teaching and learning activities in the classroom with the aim of increasing students' understanding of the Cone Slice material about Ellipses on the X and Y axes, this can be seen from the average value of the first cycle the results of the first daily examination of 83.34 and the second daily examination of 85.24 and the second cycle the results of the third daily examination of 87.42 and the fourth daily examination of 91.37 with a KKM score of 85, as well as to increase student activity, this can seen from the average student attendance of 88% to 90% in the first cycle, and the average student attendance of 95% to 100% in the second cycle, which means that students are very happy in learning mathematics with specialization, especially material about ellipses. Keyword : Ellipse Card on X and Y Axis Cone Slice Material, Specialization Mathematics Learning Media